2012
DOI: 10.1519/jsc.0b013e3182474280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Demands of Kettlebell Swing Exercise

Abstract: The aims of this study were to establish mechanical demands of kettlebell swing exercise and provide context by comparing them to mechanical demands of back squat and jump squat exercise. Sixteen men performed 2 sets of 10 swings with 16, 24, and 32 kg, 2 back squats with 20, 40, 60, and 80% 1-repetition maximum (1RM), and 2 jump squats with 0, 20, 40, and 60% 1RM. Sagittal plane motion and ground reaction forces (GRFs) were recorded during swing performance, and GRFs were recorded during back and jump squat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 8 publications
2
53
4
Order By: Relevance
“…In their study, 16 males performed two sets of 10 kettlebell swings with 16, 24, and 32 kg kettlebells. Lake and Lauder [8] reported that swing mean and peak power was greater than power recorded during a back squat and comparable with power recorded from a jump squat.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In their study, 16 males performed two sets of 10 kettlebell swings with 16, 24, and 32 kg kettlebells. Lake and Lauder [8] reported that swing mean and peak power was greater than power recorded during a back squat and comparable with power recorded from a jump squat.…”
Section: Introductionmentioning
confidence: 63%
“…To date, studies examining kettlebell science have tended to focus on either physiological variables [5][6][7] or biomechanical variables [8,9]. A number of studies have also compared kettlebell exercise to treadmill running [7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated similarities between mechanical output from 2-handed swing exercise, which is illustrated in Figure 1, and back squat and jump squat exercise (10).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the relative benefits of including kettlebell exercises, like the 2-handed swing, in athlete and general population training programs has recently increased (2,9,10,11,12,13,15,18). Research has demonstrated similarities between mechanical output from 2-handed swing exercise, which is illustrated in Figure 1, and back squat and jump squat exercise (10).…”
Section: Introductionmentioning
confidence: 99%